Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/jmv.25556
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus DNA in head and neck squamous cell carcinomas in the Free State, South Africa

Abstract: Human papillomaviruses (HPVs) have been associated with a subset of head and neck squamous cell carcinomas (HNSCCs). The aim of this study was to determine the prevalence of HPV DNA in archived formalin‐fixed paraffin‐embedded tissue from patients with histologically confirmed HNSCCs in a South African cohort. A nested PCR was used for the detection of HPV DNA targeting the L1 gene. Positive samples were confirmed using an in‐house hemi‐nested PCR targeting the E6 gene and genotyped by sequence determination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 25 publications
(70 reference statements)
1
18
0
Order By: Relevance
“…South African studies on HPV prevalence in the mouth and oropharynx are limited to 14. Of these, only 2 were conducted from oral rinse and gargle samples [22,23], 6 used oral brushes to collect samples [18,20,[32][33][34][35], and 6 were performed on formalin-fixed paraffin-embedded SCC samples [19,21,[36][37][38][39]. is highlights the importance for data on HPV infection in the head and neck region of South Africans.…”
Section: Discussionmentioning
confidence: 99%
“…South African studies on HPV prevalence in the mouth and oropharynx are limited to 14. Of these, only 2 were conducted from oral rinse and gargle samples [22,23], 6 used oral brushes to collect samples [18,20,[32][33][34][35], and 6 were performed on formalin-fixed paraffin-embedded SCC samples [19,21,[36][37][38][39]. is highlights the importance for data on HPV infection in the head and neck region of South Africans.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study contribute knowledge regarding HPV18 isolates associated with HNSCCs ( 10 , 11 ) and lay the groundwork for future research into HPV-associated HNSCC genomic characterization in South Africa.…”
Section: Announcementmentioning
confidence: 68%
“… 15 Likewise, a study of the South-African cohort found HPV DNA in 57/780 (7.3%) samples, with the highest prevalence being in the sinonasal tract (16.0%) and oropharynx (10.8%). 16 HPV16 was the most commonly detected type, being found in 26/57 (45.6%) positive samples. 16 …”
Section: Resultsmentioning
confidence: 96%
“…15 Likewise, a study of the South-African cohort found HPV DNA in 57/780 (7.3%) samples, with the highest prevalence being in the sinonasal tract (16.0%) and oropharynx (10.8%). 16 HPV16 was the most commonly detected type, being found in 26/57 (45.6%) positive samples. 16 The Human Papillomavirus (HPV) Known for its ability to infect and replicate in epithelial cells in the skin and mucosal regions, HPVs constitute a large family of non-enveloped double-stranded DNA viruses, with over 220 types having been identified.…”
mentioning
confidence: 96%